Lob Trees In The Wilderness : The Human and Natural History of the Boundary Waters - Ahlgren, C. E. (Clifford Elmer), 1922- (Book collections on Project MUSE., 2001)
Along the Minnesota-Ontario border, in the days of voyageurs, tall trees were used as guideposts in the uncharted wilderness to help fur traders and explorers find their way through the maze of lakes and portages. Branches were cut, leaving the middle of the trees bare with branches above and below. Clifford and Isabel Ahlgren use nine native trees to serve as lob trees for this book, an ecological history of human activity in the Quetico-Superior wilderness area.